An examination of the effects of venture capitalists on the alliance formation activity of entrepreneurial firms - Blevins, Dane P.; Ragozzino, Roberto (Strategic Management Journal, 2018)
[Research summary: Alliances offer benefits such as access to capital, knowledge, and markets. Yet, due to their lack of legitimacy, entrepreneurial firms find it challenging to engage in alliances. Thus, it is important to examine which factors may drive alliance formation for entrepreneurial firms. We examine whether the presence of venture capitalists (VCs) is such a factor. Whereas current research suffers from endogeneity concerns that make the comparison of VC- and non-VC-backed firms problematic, our empirical design reduces this problem. Overall, we find that the presence of a VC and a VC's experience with taking firms public are positively associated with entrepreneurial firms' alliance formation, and that VCs are more active in forming an alliance when the exit outcome is an acquisition, rather than going public. Managerial summary: Alliances can be of fundamental importance to the growth of entrepreneurial firms. However, because entrepreneurial firms hold limited resources, their access to alliances may be limited. We study whether entrepreneurial firms backed by venture capitalists (VCs) are more likely to enter into alliances than firms without VC backing. A major problem with this sort of analysis is that VCs may cherry pick the best firms, which in turn are more likely to engage in alliances to begin with, irrespective of VCs. Accordingly, we control for the quality of funded firms, and therefore, isolate the VCs' contribution to alliance formation. In doing so, we find support for the importance of the role VCs play in entrepreneurial firms' alliance formations.]